2004
DOI: 10.1152/jn.00744.2003
|View full text |Cite
|
Sign up to set email alerts
|

Median and Dorsal Raphe Neurons Are Not Electrophysiologically Identical

Abstract: The dorsal (DR) and median raphe (MR) nuclei contain 5-hydroxytryptamine (serotonin, 5-HT) cell bodies that give rise to the majority of the ascending 5-HT projections to the forebrain limbic areas that control emotional behavior. In the past, the electrophysiological identification of neurochemically identified 5-HT neurons has been limited. Recent technical developments have made it possible to re-examine the electrophysiological characteristics of identified 5-HT- and non-5-HT-containing neurons. Visualized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
137
0
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 36 publications
13
137
0
8
Order By: Relevance
“…Once the whole cell configuration was obtained, cell characteristics were recorded using current clamp techniques. The cellular characteristics were measured as previously described (Beck et al, 2004). Following the collection of cell characteristics, the pyramidal cell was returned to voltage clamp mode at À60 mV.…”
Section: Whole-cell Recording In Ca1 Pyramidal and Dorsal Raphe Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the whole cell configuration was obtained, cell characteristics were recorded using current clamp techniques. The cellular characteristics were measured as previously described (Beck et al, 2004). Following the collection of cell characteristics, the pyramidal cell was returned to voltage clamp mode at À60 mV.…”
Section: Whole-cell Recording In Ca1 Pyramidal and Dorsal Raphe Neuronsmentioning
confidence: 99%
“…Brain slice immunohistochemistry for biocytin and tryptophan hydroxylase was conducted to determine whether the neurons recorded from the pet + / + mice contained 5-HT as previously described (Beck et al, 2004). Slices from the pet1 À/À mice were also processed to detect expression of the lacZ marker of 5-HT precursor neurons as previously described (Scott et al, 2005), but using chicken anti-b-galactosidase (1 : 1000, Abcam) and FITC-conjugated goat anti-chicken (1 : 250, Abcam) antibodies.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Interestingly, previous studies have reported differences between the neuronal properties of the DRN and MRN. 31 It is tempting to speculate that the MRN neuronal population sampled in this study may have corresponded to rhombomere 2−3 derived neurons. The availability of mice carrying intersectionally tagged neurons from these cell populations should greatly facilitate further exploration of this issue.…”
mentioning
confidence: 86%
“…7,8 Moreover, in vitro patch-clamp studies conducted in brain slices demonstrated a high degree of variability in the passive and active membrane properties of 5-HT neurons. 9,10 Finally, anatomical and electrophysiological studies showed that 5-HT1A receptors are not only expressed in 5-HT neurons, but also in other neuronal classes in the raphe nuclei. 10−12 Together these evidence call to re-evaluate the definition of serotonergic cell, and to determine which methods are most appropriate for their identification.…”
mentioning
confidence: 99%
“…11,16 In addition, electrophysiological studies where hyperpolarizing responses elicited by superfusion of a 5-HT1A agonist were assessed, found a considerable number of nonresponding identified serotonergic cells. 9,10,12,25 We hypothesized that while following the classic dogma to identify 5-HT neurons, many investigators have discarded data involving 5-HT1A-negative serotonergic neurons.…”
mentioning
confidence: 99%